How Does a History of Trauma Affect the Experience of Imprisonment for Individuals in Women’s Prisons: A Qualitative Exploration - Kelman, Jude (Women & criminal justice, 2024)
The majority of women in prison have experienced prior traumatic events. Imprisonment can also be considered a traumatic experience. Research exploring how imprisonment affects women with trauma histories is scarce. To examine this, qualitative interviews were conducted with 50 participants imprisoned in three women’s prisons in England. Four overarching themes were identified using thematic analysis: the traumatizing prison system; triggering power dynamics; trust in relationships; and surviving and thriving. Aspects of the prison environment and staff behavior were experienced as triggering and traumatizing, while peer relationships provided some mitigation of these difficulties. These findings have implications for the design of women’s prisons, improvements in staff recruitment and training, and the implementation of trauma-informed care for individuals in women’s prisons.